Lessons for and from the COVID-19 pandemic response - An appraisal of guidance for the public health management of Invasive Meningococcal Disease - Brianna R. Morello; Adriana Milazzo; Helen S. Marshall; Lynne C. Giles (Elsevier, 2021)
Background: COVID-19 has focussed public attention on the management of communicable disease like never before. Surveillance, contact tracing, and case management are recognised as key components of outbreak prevention. Development of guidance for COVID-19 has drawn from existing management of other communicable diseases, including Invasive Meningococcal Disease (IMD). IMD is a rare but severe outcome of Neisseria meningitidis infection that can be prevented through vaccination. Cases still occur sporadically, requiring ongoing surveillance and consistent management. To this end, national and international public health agencies have developed and published guidance for identification and management of IMD cases. Aim: To assess national and international guidelines for the public health management of IMD, with a focus on the recommendations for identification and management of "close contacts" to IMD cases. Methods: Guidelines from six national and international public health agencies were assessed using a modified version of the Appraisal of Guidelines, Research and Evaluation (AGREE II) Instrument in four key domains: stakeholder involvement, developmental rigour, clarity, and applicability. A direct comparison of terminology and recommendations for identification and management of close contacts to IMD cases was also conducted. Results: Guidelines from Europe and the United Kingdom rated most highly using the AGREE II Instrument, both presenting a clear, critical assessment of the strength of the available evidence, and the risks, costs, and benefits behind recommendations for management of close contacts. Direct comparison of guidelines identified inconsistencies in the language defining close contacts to IMD cases. Conclusion: Discrepancies between guidelines could be due to limited evidence concerning mechanisms behind disease transmission, along with the lack of a consistent process for development and review of guideline recommendations. COVID-19 management has demonstrated that international collaboration for development of public health guidance is possible, a practice that should be extended to management of other communicable diseases.